Mental Health Correlates of Autistic and ADHD Traits in Secondary School Students - Japnoor Garcha; Andrew P. Smith; Arwel James (Brain Sciences)
Background: Recent research has examined the associations between autistic traits and the well-being of students. This research has also included measures of ADHD and mental health. Methods: To understand the association and interaction of well-being and mental health with autistic traits (AQ) and attention deficit hyperactivity disorder (ADHD) traits, a survey was given to 578 secondary school students. The survey used the well-being process questionnaire (WPQ), the autism spectrum quotient, the ADHD self-report scale, and the Strengths and Difficulties questionnaire (SDQ). Results: The analysis conducted using SPSS showed that there was a significant correlation between anxiety, depression, AQ, and ADHD. Anxiety and depression were also significantly correlated with all well-being and SDQ variables. The regression analysis, including psychosocial predictors of well-being, anxiety, depression, ADHD, and AQ, showed that anxiety and depression were strongly associated with well-being outcomes. In contrast, AQ and ADHD were associated with hyperactivity, peer problems, and reduced prosocial behaviour. The associations between anxiety, depression, and well-being outcomes were stronger than with either AQ or ADHD. Conclusions: This study extends previous research from university samples to a secondary school sample. This shows the importance of investigating associations between subclinical traits and psychological symptoms in early adolescence, as this will lead to better-informed prevention and early intervention strategies.